Kontribusi Young Interfaith Peacemaker Community (YIPC) dalam Menyebarkan Narasi Kontra Radikalisme - M Royyan Nafis FW (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
This research departs from the problem of the ideology of radicalism that developed in Indonesia. The ideology of radicalism in its spread through social media targets many young people as their targets. This is evidenced by the presence of several young people who participated in becoming sympathizers of terrorism and even carried out acts of terror on the basis of religion. The subject of this research is the Young Interfaith Peacemaker Community (YIPC) organization and the object is the YIPC program that can be used to spread counter radicalism narratives. The objectives of this research are: exploring the YIPC program in spreading counter radicalism narratives, analyzing the manifestations of the YIPC Program in spreading counter radicalism narratives, and exploring the Role of YIPC in spreading counter radicalism narratives. This research is qualitative research analyzed descriptively. Data was collected through field observations, interviews, and documents relating to the YIPC program as primary sources and books, journals, magazines, and internet information as secondary sources. The results of this study indicate that YIPC has a role as a forum and interfaith youth facilitator who concentrates on the concept of peace education and interfaith dialogue based on the scriptures to build peace through peaceful cadres by spreading fourteen basic values of peace aimed at reducing radicalism and ideological intolerance.